Upregulation of C/EBPα contributes to colorectal cancer growth, metastasis and indicates poor survival outcome - Mi, Lan; Hu, Kai; Wen, Xianzi; Sun, Jing; Wu, Aiwen; Wang, Mingliang; Zheng, Minhua; Zang, Lu; Ji, Jiafu (American journal of cancer research, 2018)
The function and clinical implication of transcription factor CCAAT/enhancer-binding protein α (C/EBPα) in colorectal cancer (CRC) still remains undefined. In fact, C/EBPα has long been considered as a tumor suppressor in hematopoietic system and also found lowly expressed in numerous solid tumors. However, our results here for the first time showed that C/EBPα was unexpectedly upregulated and was an independent prognostic marker for patients with CRC. We therefore aimed to explore the detailed role and mechanisms of C/EBPα in CRC. Our investigation demonstrated that C/EBPα promoted tumor growth both in vitro and in vivo. In addition, suppression of C/EBPα inhibited cell proliferation by inducing G1 phase arrest and inducing apoptosis. Also, C/EBPα enhances CRC cells migration and invasion in vitro as well as metastasis in vivo through regulating EMT. Mechanistically, C/EBPα exerts its oncogenic role by targeting c-Myc/cyclin D1 mediated by β-catenin involved pathway and we provide evidence indicating that cytoplasmic exclusion of C/EBPα might contribute to its oncogenic function in tumor progression. In conclusion, C/EBPα acts as an oncogene in CRC and could be a potential biomarker of colon carcinogenesis.
Gesehen am 14.04.2020